The Effect of Colour on Humans Psychology (International Journal of Food and Nutritional Sciences, 2022)
The colour can be explained as the feature of any item that can be described using hue, brightness, and saturation. In physics, the term "colour" refers particularly to electromagnetic radiation having a certain spectrum of visible wavelengths. Research in the field of colour psychology examines how colour affects human behaviour and decision-making. This paper explores the effect of colour on human psychology in a very detailed manner and also discusses the different effects caused by the different colours that change the mood accordingly in humans. When employed in marketing, for instance, certain colours may influence how consumers view a brand in subtle ways, like how some tones might enhance hunger.